2021
DOI: 10.18632/aging.203420
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0134111 promotes osteoarthritis progression by regulating miR-224-5p/CCL1 interaction

Abstract: Mechanical, metabolic, inflammatory, and immune factors contribute to the development of osteoarthritis (OA), a joint disease characterized by cartilage destruction. The circular RNA (circRNA) hsa_circ_0134111 is upregulated in the cartilage of OA patients; however, its potential role in OA pathogenesis and progression remains unexplored. In this study, the effects of hsa_circ_0134111 knockdown were evaluated in primary human chondrocytes treated with IL-1β to simulate OA, as well as in a rat model of OA. Hsa_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…disclosed that circ_0088036 accelerated the progression of rheumatoid arthritis via miR-140-3p-related sirtuin-1 (SIRT1) upregulation [ 32 ]. Additionally, circ_0134111 promoted OA chondrocyte damage by inhibiting miR-224-5p to induce overexpression of CC motif ligand 1 (CCL1) [ 33 ]. Circ_0045714 increased phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) level to regulate IL-1β-stimulated chondrocyte injury via serving as a ceRNA of miR-331-3p [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…disclosed that circ_0088036 accelerated the progression of rheumatoid arthritis via miR-140-3p-related sirtuin-1 (SIRT1) upregulation [ 32 ]. Additionally, circ_0134111 promoted OA chondrocyte damage by inhibiting miR-224-5p to induce overexpression of CC motif ligand 1 (CCL1) [ 33 ]. Circ_0045714 increased phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) level to regulate IL-1β-stimulated chondrocyte injury via serving as a ceRNA of miR-331-3p [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 42 ] showed that knockdown of circ_0134111 alleviated osteoarthritis symptoms through sponging miR-224-5p. Liu et al [ 34 ] also found that circ_0134111 induced osteoarthritis development through modulating the miR-224-5p/CCL1 axis. In our study, we found that the same circRNA was upregulated in IDD tissue and its overexpression promoted aberrant NP cell phenotypes, including proliferation, cytokine expression, and ECM degradation…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggested that circRNAs play critical roles in cell functions, such as apoptosis, growth, metabolism, and ECM synthesis [ 28 , 29 ] circRNAs have also been promulgated as therapeutic targets in different diseases including neurological dysfunction, metabolic diseases, cancers, and cardiovascular diseases [ 30 33 ]. For instance, a recent study showed that circ_0134111 could induce osteoarthritis development through regulating miR-224-5p/CCL1 and miR-515-5p-SOCS1 axes [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For apoptosis analysis, 10 μL of annexin V-fluorescein isothiocyanate and 5 μL of PI were added. A FACSCalibur flow cytometer was employed for detection (BD Biosciences) [19].…”
Section: Flow Cytometrymentioning
confidence: 99%